Ketersediaan dan Pemanfaatan Ruang Terbuka Hijau di Kampus UKDC Surabaya - Josephine Roosandriantini; Heristama Anugerah Putra (ARSITEKTURA, 2021)
Increasing temperatures and changes in global weather are currently affecting all countries, including Indonesia. This problem is what we can call global warming. The city of Surabaya in particular experiences this problem where there is a shift in time related to the dry season and the rainy season. The formation of green open spaces is important in a city to reduce the impact that is imposed globally. The main target expected is to take part in reducing the temperature in the city of Surabaya so that the ecological balance in it is maintained even though it is small or limited to existing sites. This is based on regional regulations regarding the proportion of green open space that must be presented according to data from Bappeko Surabaya. The method in research using literature studies, observational studies, and study designs in a form tailored to the analysis. The result of this research is to add the availability and utilization of green open space in the form of vertical vegetation in the UKDC campus building to provide additional green open space for both the UKDC campus and the city of Surabaya. So in other words, the new UKDC campus building can provide additional green open space to achieve the availability of green open space on private land.